Lake Michigan - Borzutzky, Daniel (Pitt poetry series., 2018)
Lake Michigan, a series of 19 lyric poems, imagines a prison camp located on the beaches of Chicago that is privatized, racially segregated, and overrun by a brutal police force. Thinking about the ways in which economic policy, racism, and militarized policing combine to shape the city, Lake Michigan's poems explore the themes of estrangement, state violence and capitalist exploitation, and take a hard look at neoliberal urbanism in the historic city of Chicago.